OPTIMASI TEKNOLOGI PRODUKSI NANOFIBER SELULOSA BAMBU AMPEL (Bambussa vulgaris) - . Fakhruzy (Jurnal Biofisika, 2013)
Bamboo Ampel (bambussa vulgaris) is one of the lignocellulose  -containing plants. Easy cultivation  and a brief period of growth illustrate  the potential of bamboo as a substitute  for the use of synthetic fibers. Production process to produce fibers in the size of the nanofiber is the focus in this study. Semi-chemical pulping processed with NaOH done to soften and separate the cellulose fibers. Mechanical processed  with disc refiner for atrial fibers (for 4, 7, 10, 13, and 16 times) do well in order to know fibrillation  process  optimization.  Microfibrils  which  are  formed  during  the  ultrasonic wave  treatment  applied  for  2  hours  to  change  the  size  of  the  microfibrils  into  a nanofiber.  The  results  of  the  treatment  were  dried  with  freeze  dryer,  and  then analyzed using a scanning electron microscopy (SEM ) and X - ray diffraction ( XRD ). The results of the SEM analysis showed that the duration of mechanical processes will affect the size of the resulting cellulose microfibrils. Mechanical process 16 times, which has been treated ultrasonic , produce cellulose microfibrils with 480   nm size and crystallinity of cellulose based on the JCPDS ( ICDD ) cellulose ( C6H10O5 ) X has a monoclinic structure for a = 7.87, b = 10.31, c = 10, 13 and α = Ɣ = 90 ≠ β =122.0 , hkl values ( position crystalline cellulose ) are in the field of 002 ( 20 639 ).